2014
DOI: 10.1186/s12933-014-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-1 receptor antagonist anakinra improves endothelial dysfunction in streptozotocin-induced diabetic rats

Abstract: BackgroundEndothelial dysfunction is a crucial early phenomenon in vascular diseases linked to diabetes mellitus and associated to enhanced oxidative stress. There is increasing evidence about the role for pro-inflammatory cytokines, like interleukin-1β (IL-1β), in developing diabetic vasculopathy. We aimed to determine the possible involvement of this cytokine in the development of diabetic endothelial dysfunction, analysing whether anakinra, an antagonist of IL-1 receptors, could reduce this endothelial alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 71 publications
7
95
0
4
Order By: Relevance
“…In addition, a large body of preclinical data showed that IL-1b is involved strongly in the progression of atherosclerosis [69,70]. During the inflammatory process occurring in RA, it has been shown that TNF may contribute to endothelial dysfunction [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a large body of preclinical data showed that IL-1b is involved strongly in the progression of atherosclerosis [69,70]. During the inflammatory process occurring in RA, it has been shown that TNF may contribute to endothelial dysfunction [71].…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic and flavonoid contents was determined, and the result showed 51.04 ± 0.91 mgGAE/g and 0.13 ± 0.01 mg of catechin/g content in dry leave extract, respectively. Likewise, other studies that found phenolic at 3.21 mg GAE/g, 33 37.38 ± 0.49 mg GAE/g, 17 78.8 g GAE/100g extract, 18 258.4±7.45 mg GAE/g, 16 7.51 to 12.06 mg GAE/g, 34 and flavonoid contents at 159.61±12.79 mg QE/g (Quercetin equivalent), 16 2.80 to 3.59 mg QE/g 34 depended on parts of plant collection and solution extracted. This compon ents suggest antioxidant activities of L. leucocephala, as confirmed in Table 1.…”
Section: Conclusion and Discussionmentioning
confidence: 57%
“…With histology of vascular cells, the result showed that the vascular cells were obviously dead in HUVC-induced pre-obese condition. In this condition of increasing extracellular glucose, it was suggested to induce endothelial cell dysfunction by increased activation of NADPH oxidase and IL1β, 35,36,37 which might eventually lead to senescence of the cells. When 0.05 mg/mL of leave extracts were pre-incubated in the system, the overall of vascular cells have been found resembling the control group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This effect was partially prevented by incubation of the isolated blood vessels with Apocynin (NADPH oxidase inhibitor). Also, normal endothelial function was restored by incubation with a NADPH oxidase, cyclooxygenase-2 (COX-2), eNOS inhibitors, and superoxide dismutase [79], proving the role of oxidative stress in IL-1b-induced ED.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 94%